Efektifitas Clinical Supervision terhadap Peningkatan Class Management Abilities Guru di Sekolah Dasar - Muhsin, H (UNDIKMA, 2021)
This study was to determine the effectiveness of clinical supervision to improve the class management abilities of elementary school teachers. The research method uses action research based on clinical supervision in three cycles. Implementation of clinical supervision was attended by 24 representative teachers from 10 elementary schools in the Education Office of North Batukliang District, Central Lombok. Data collection was carried out through classroom observations and class management coaching tests and was described based on the results of the teacher's mastery achievement analysis. The results showed that the percentage of completeness in each cycle was obtained 37.5% in cycle-I, 62.5% in cycle-II, and 100% for cycle-III. It can be concluded that the implementation of clinical supervision is effective to improve the ability of elementary school teachers in conducting classroom management.